The pirate's coin - Malone, Marianne (Malone, Marianne. Sixty-eight rooms adventure., 2013)
A magical coin coin leads sixth-graders Ruthie and Jack to 1753 Massachusetts and to Jack's pirate ancestor when they return to the Art Institute of Chicago's miniature Thorne Rooms on a mission to restore an African American family's reputation.